2022
DOI: 10.12821/ijispm060303
|View full text |Cite
|
Sign up to set email alerts
|

To schedule or not to schedule? An investigation of meetings as an inter-team coordination mechanism in largescale agile software development

Abstract: Coordination of teams is critical when managing large programmes that involve multiple teams. In large-scale software development, work is carried out simultaneously by many developers and development teams. Results are delivered frequently and iteratively, which requires coordination on different levels, e.g., the programme, project, and team levels. Prior studies of knowledge work indicate that such work relies heavily on coordination through "personal" modes such as mutual adjustment between individuals or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
1
13
0
3
Order By: Relevance
“…Previous research on large-scale agile development practices has identified and described several individual inter-team coordination mechanisms. Examples include planned and unplanned meetings [15], [47], [48], communication platforms and tools such as Slack and JIRA [20], groups of representatives (often referred to as communities of practice) [3], [21]- [23] boundary-spanner roles such as product owners and architects [24], [54], and open spaces for inter-team coordination [5]. We revisit existing research on inter-team coordination mechanisms in Section 5.…”
Section: Inter-team Coordination Mechanisms In Largescale Agilementioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on large-scale agile development practices has identified and described several individual inter-team coordination mechanisms. Examples include planned and unplanned meetings [15], [47], [48], communication platforms and tools such as Slack and JIRA [20], groups of representatives (often referred to as communities of practice) [3], [21]- [23] boundary-spanner roles such as product owners and architects [24], [54], and open spaces for inter-team coordination [5]. We revisit existing research on inter-team coordination mechanisms in Section 5.…”
Section: Inter-team Coordination Mechanisms In Largescale Agilementioning
confidence: 99%
“…Successful coordination of activities such as iteration and sprint planning, backlog grooming [15], bottom-up architecture design, product demonstrations, and continuous deployment and delivery [5], [16] dictate the success or failure of large-scale agile software development. Therefore, dependencies must be managed continuously throughout the development life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The group mode of coordination in large-scale agile development was further analysed in a study of two empirical cases, with a focus on changes in coordination modes over time (Moe et al 2018). These changes included transitions from scheduled to unscheduled meetings and from unscheduled to scheduled meetings.…”
Section: Group Mode Coordinationmentioning
confidence: 99%
“…Practices for inter-team coordination have been proposed in the agile community to reduce the negative impacts of agile while also maintaining the positive impacts of teamwork stemming from agile ways of working [5]. These practices include, for example, scheduled and unscheduled meetings, as well as the use of shared visualization tools [6]. Moreover, many organizations use large-scale agile frameworks that come with pre-determined coordination practices and tools aimed at improving the inter-team coordination of software development.…”
Section: Introductionmentioning
confidence: 99%